PELATlHAN GARAP IRINGAN PAKELlRAN GAYA SURAKARTA DI SANGGAR GUYUP RUKUN JEBRES SURAKARTA - Sunarto Sunarto (Abdi Seni, 2016)
The main elements ofpakeliran cover garap sabet, iringan, and catur. The three main elements have the same function in supporting the whole performance. During this time, sabet and catur are given more attention than iringan (accompaniment). For the reason, the quality of pakeliran presentation in wayang performance must be improved for wayang kulit performance contains high values that are able to form Indonesian s attitude and behavior: The improvement can be executed through nonformal education, for example, in studio Guyup Rukun. The training of iringan or pakeliran karawitan (Javanese traditional music) in Sanggar Guyup Rukun uses the method of appreciation, discussion, and demonstration. The result, based on the method, is that students in the studio are able to master Ketawang Gendhing Kabor laras slendro pathet nem, Ladrang Gleyong laras pelog pathet nem, Kemuda laras pelog pathet nem and palaran Pangkur, as well as Ladrang Kalongking laras pe log pathet nemo Other material mastered by the students include gendhing and sulukan for wayang golek.Key words: studio, Guyup Rukun, pakeliran accompaniment, training